INVESTIGATION OF THE INFLUENCE OF THE ROLLING STOCK DYNAMICS ON THE INTENSITY OF USING THE RAILWAY TRACK ELEMENTS - Bondarenko, I. O.; Neduzha, L. O. (Science and Transport Progress, 2019)
Purpose. The main purpose of this work is to research deformability parameters of the railway track under various operating conditions as the initial data for the formation of forced oscillations of rolling stock and the trackform use intensity. Methodology. For the research, an original model of the trackform, described with using the basic concepts of the theory of elasticity and the propagation of elastic waves was developed. Findings. It has been established that the ratio between the intensity of work of elements and the trackform, as criteria for deformability, can be used as the estimated parameters of the functionally safe operation of the track. It can be the basis for the classification of critical track states under which it had to perform work to restore its working capacity in order to ensure the required level of efficiency of use construction during the service life. Originality. Trackform and parameters of the elements of the track superstructure and substructure can be described using the railway tracks deformability behaviour. In the future this conclusion will help to increase the efficiency of the dynamic properties of rolling stock when designing and maintain in readiness the infrastructure while in operation. Practical value. Changes in the regulatory framework of rail transport in recent years provide for the observance of its functional safety, therefore, the question of the need to assess the impact of rolling stock on the way to be regarded as a dynamic process with consideration to the deformability resistance track. This research provides a basis for record of the stiffness of deformation that allows creating the regulatory framework for safety and functional safety of the railway track in Ukraine.